Effect of Return On Assets, Return On Equity and Earning Per Share on the price of shares at PT. Gajah Tunggal tbk - Ilham, Ilham (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to determine the effect of Return on Assets, Return on Equity and Earning Per Share on stock prices at PT. Gajah Tunggal Tbk. The method used was explanatory research with a sample of 8-year financial statements in the form of a panel PT. Gajah Tunggal Tbk. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Return on Assets have a significant effect on stock prices by 53.4%, hypothesis testing obtained significance of 0.040 <0.05. Return on Equity has a significant effect on stock prices by 83.0%, hypothesis testing obtained significance of 0.002 <0.05. Earning Per Share has a significant effect on the stock price of 97.9%, the hypothesis test obtained significance 0,000 <0.05. Return on Assets, Return on Equity and Earning Per Share simultaneously have a significant effect on the stock price of 99.5%, the hypothesis test obtained significance 0,000 <0.05.